2016
DOI: 10.1027/1866-5888/a000160
|View full text |Cite
|
Sign up to set email alerts
|

Supportive Climate and Its Protective Role in the Emotion Rule Dissonance – Emotional Exhaustion Relationship

Abstract: Abstract. Emotion work, or the requirement to display certain emotions during service interactions, may produce burnout when these emotions are not truly felt – emotion rule dissonance. Building on the support-buffering model we hypothesized that a supportive climate should provide emotional resources to employees protecting them against strain from emotion work. We tested this multilevel prediction in a sample of 317 front-line employees nested in 99 work units at large Spanish hotels and restaurants. Our res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 59 publications
0
12
0
Order By: Relevance
“…On the other hand, previous research findings indicate that persistent exposure to a given work stressor may be detrimental even for those with a highly robust personality ( Nielsen et al, 2008 ; Ilies et al, 2011 ; Britton et al, 2012 ; Reknes et al, 2016 ). Organizations should therefore not only rely on the individual dispositions of their employees alone, but also provide organizational resources that may help their workers deal with the potential impact of emotional dissonance, such as a supportive organizational climate ( Kinman et al, 2011 ; Ortiz-Bonnín et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, previous research findings indicate that persistent exposure to a given work stressor may be detrimental even for those with a highly robust personality ( Nielsen et al, 2008 ; Ilies et al, 2011 ; Britton et al, 2012 ; Reknes et al, 2016 ). Organizations should therefore not only rely on the individual dispositions of their employees alone, but also provide organizational resources that may help their workers deal with the potential impact of emotional dissonance, such as a supportive organizational climate ( Kinman et al, 2011 ; Ortiz-Bonnín et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“… Kinman et al (2011) showed that social support buffers the negative impact of emotional demands on emotional exhaustion among teachers. Ortiz-Bonnín et al (2016) recently found in their study of hotel employees that a supportive climate had a buffering effect on the relationship between emotional dissonance and emotional exhaustion, meaning that supportive climate protects employees who experience emotional dissonance from suffering emotional exhaustion.…”
Section: Introductionmentioning
confidence: 99%
“…Since the early 1970s, there has been a major redistribution of employment from industry into the service sector ( Dolphin, 2015 ), and service jobs have become the major form of employment in European countries ( Paoli and Merllié, 2012 ). Through their direct contact with customers and clients, service employees are expected to display emotions according to the organization’s explicit or implicit emotional display rules ( Brotheridge and Grandey, 2002 ; Ortiz-Bonnín et al, 2016 ). Regulating feelings to display the appropriate emotion during social interactions has thereby emerged as a job demand for many employees ( Zapf, 2002 ).…”
Section: Introductionmentioning
confidence: 99%
“…Constant face-to-face interaction with customers has increasingly emphasised the emotional dynamic involved, with academic and organisational literature paying close attention to emotional labour strategies applied by workers. Indeed, relationships with customers can represent a demanding aspect among service workers, who need to effectively manage their own emotions and feelings to ensure a positive customer experience [7]. To this purpose, workers must comply with the set of norms, labelled as emotional display rules, that organisations develop in order to define who is allowed to exhibit what specific emotional expressions, and under which circumstances [8].…”
Section: Introductionmentioning
confidence: 99%